Use of two wavelengths in microscopic TV holography for nondestructive testing - Upputuri, Paul Kumar (2014)
Single wavelength TV holography is a widely used whole-field noncontacting optical method for nondestructive testing (NDT) of engineering structures. However, with a single wavelength configuration, it is difficult to quantify the large amplitude defects due to the overcrowding of fringes in the defect location. In this work, we propose a two wavelength microscopic TV holography using a single-chip color charge-coupled device (CCD) camera for NDT of microspecimens. The use of a color CCD allows simultaneous acquisition of speckle patterns at two different wavelengths and makes the data acquisition as simple as that of the single wavelength case. For the quantitative measurement of the defect, an error compensating eight-step phase-shifted algorithm is used. The design of the system and a few experimental results on small-scale rough specimens are presented.